2019
DOI: 10.1186/s40795-019-0294-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency in pregnant women and their babies in Bhaktapur, Nepal

Abstract: Background: Vitamin D deficiency has been observed worldwide in pregnant women and their newborns. Maternal vitamin D deficiency can lead to deficiency in their newborn baby and has been linked with various complications during pregnancy and delivery. There is risk of premature delivery and it is associated with high neonatal mortality. Methods: Seventy-nine pregnant women who were admitted to the Siddhi Memorial Hospital for delivery and their newborn babies were enrolled in the study. Maternal blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 18 publications
8
16
0
Order By: Relevance
“…The prevalence of vitamin D deficiency in this study was 14.1%. The finding is in line with several studies reported from different countries across the globe that show vitamin D deficiency prevalence ranging from 4-60% [20][21][22][23][24][25]. A previous pilot study carried out on a convenient sample of 40 parturient women at Nnamdi Azikiwe University Teaching Hospital, Nnewi Nigeria showed a vitamin D deficiency level of 7.5% [26] -almost half of our present findings.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of vitamin D deficiency in this study was 14.1%. The finding is in line with several studies reported from different countries across the globe that show vitamin D deficiency prevalence ranging from 4-60% [20][21][22][23][24][25]. A previous pilot study carried out on a convenient sample of 40 parturient women at Nnamdi Azikiwe University Teaching Hospital, Nnewi Nigeria showed a vitamin D deficiency level of 7.5% [26] -almost half of our present findings.…”
Section: Discussionsupporting
confidence: 93%
“…Our result is also in congruence with another study by Shrestha D et al 18 In this study, the authors had done cord blood screening showing mean calcium of 8.6 ± 0.9 mg/dl. Another study done by Do mean calcium of 7.1 ± 0.84 mg/dl.…”
Section: Discussionsupporting
confidence: 92%
“…However, our result is consistent with various studies done in abroad 7,11,12 as well as in Nepal. 18 These studies had showed close relation of neonatal hypocalcaemia with maternal low vitamin D level. This may be the result of clothing culture, food habit, skin colour as well as similar races.…”
Section: Discussionmentioning
confidence: 97%
“…[ 25 ] Also, vitamin D may increase the risk of iatrogenic preterm birth by increasing the occurrence of pregnancy complications. [ 26 ] In addition, vitamin D deficiency could cause a decrease in the immune tolerance of pregnant women, resulting in a relative or absolute low of regulatory T cells, which significantly weakened the body's immunosuppressive effect, and thus could not suppress the excessive immune response and increased the risk of miscarriage. [ 27 ] However, at present, the mechanism of how maternal vitamin D deficiency causes SGA during pregnancy has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%